Fixed effects analysis of the incidence of cardiovascular outcomes under managed care following the managed care backlash. Issue 23 (5th June 2020) - Dugan, Jerome A.
Abstract : Abstracts: To examine the impact of increased managed care activity on 30-day readmission and mortality for acute myocardial infarctions and congestive heart failure in U.S. hospitals following the managed care backlash against managed care cost containment practices. The Centers for Medicare and Medicaid Services (CMS) Hospital Compare files, CMS Hospital Cost Report, CMS Medicare Advantage Enrollment files, and Health Resources and Services Administration Area Resource File data for the period 2008 to 2011 were used to construct the study sample. Multivariate fixed effects regression with robust standard errors, hospital fixed effects, and year fixed effects were used to estimate the impact of managed care penetration on adverse cardiovascular outcomes. Our primary outcome measures were readmission and mortality for patients discharged with acute myocardial infarction and congestive heart failure for acute, non-federal hospitals with emergency rooms. To examine effects of hospital ownership status, not-for-profit hospitals were compared to proprietary hospitals. The main analysis revealed that an increase in managed care penetration was associated with a decline in both 30-day readmission and mortality for acute myocardial infarction and congestive heart failure. In the hospital ownership analysis, only the acute myocardial infarction results for proprietary hospitals was statistically significant. All hospital types reported similar congestive heart failure trends as the full sample; however, proprietary hospitals reported greater declines in readmission and mortality. Increased managed care activity is associated with reductions in hospital readmission and mortality following the legislative and consumer backlash against managed care, with differential impacts across hospital ownership type. These finding highlights the important role of managed care in creating quality improvements in the delivery of care in the hospital setting.